Analisis Yuridis Terkini Terhadap Tugas Common Law And Fidusia Direktur di Inggris, Amerika, Kanada Dan Indonesia - Yafet Yosafet Wilben Rissy (Faculty of Law, Universitas Gadjah Mada, 2022)
Abstract This article discusses the role of the Supreme Court in defending the principle of the supremacy of the constitution. This article argues that the Supreme Court has inherent judicial authority to defend the supremacy of the constitution over legislation even the Constitution itself does not confer the authority explicitly. The supremacy of the constitution is a fundamental constitutional principle that binds all public authorities of the State. As part of the public authorities, the Supreme Court has a duty to disregard unconstitutional legislation. To do this the Supreme Court has judicial discretion to set aside legislation whenever he assumes that the legislation in question is contrary to the Constitution before it can be applied in a concrete case. Unlike the Constitutional Court, the Supreme Court does not have authority to invalidate unconstitutional legislation. The Supreme Court may assess the constitutionality of legislation in the sense of weak-form judicial review. Whereas the Constitutional Court’s authority to review the constitutionality of legislation is a strong-form judicial review. The two models of judicial review should work together because Indonesia adopts the supremacy of the constitution principle, instead of the supremacy of the Constitutional Court. Intisari Artikel ini mendiskusikan peran Mahkamah Agung dalam mempertahankan asas supremasi konstitusi. Artikel ini berargumen bahwa Mahkamah Agung memiliki kewenangan yudisial inheren dalam mempertahankan supremasi konstitusi terhadap undang-undang meskipun Konstitusi sendiri tidak memberikan kewenangan eksplisit. Supremasi konstitusi adalah asas konstitusional fundamental yang mengikat seluruh badan pemerintah. Sebagai bagian dari badan pemerintah, Mahkamah Agung memiliki diskresi yudisial untuk mengesampingkan undang-undang manakala dia beranggapan bahwa undang-undang tersebut bertentangan dengan konstitusi sebelum menerapkannya ke dalam kasus konkret. Tidak seperti Mahkamah Konstitusi, Mahkamah Agung tidak memiliki kewenangan untuk menyatakan undang-undang tidak memiliki kekuatan mengikat. Mahkamah Agung dapat menilai konstitusionalitas undang-undang dalam pengertian weak-form judicial review. Sementara kewenangan Mahkamah Konstitusi untuk menguji konstitusionalitas undang-undang adalah strong-form judicial review. Kedua model pengujian yudisial tersebut seyogianya berjalan bersama karena Indonesia mengadopsi asas supremasi konstitusi, ketimbang supremasi Mahkamah Konstitusi.